HPLC Analysis and Antioxidant Evaluation of Acteoside-Rich Osmanthus fragrans Extracts - Sung-Ho Lee; Seong-Wook Seo; Seung-Yub Song; Deuk-Sil Oh; Jung-Hyun Shim; Goo Yoon; Ye-Yong Choi; Do-Kyung Kim; Jae-Sung Kim; In-Soo Yoon; Seung-Sik Cho (Journal of Food Quality)
A method for the separation and quantification of acteoside by reverse-phase high-performance liquid chromatography (HPLC) was developed and validated. Hot water and ethanolic extracts of Osmanthus fragrans leaves and flowers were analyzed for acteoside content. Excellent linearity was obtained, with an r2 higher than 0.999. The precision, specificity, and accuracy of our method were excellent, suggesting that it can be conveniently used for the quantification of acteoside in the crude extract of O. fragrans. The hot water and ethanol extracts were analyzed, and their biological activities were tested. The extraction yields, marker (acteoside) contents, and antioxidant activities of the leaf and flower extracts were analyzed. The antioxidant activity was confirmed by measuring the 2,2-diphenyl-2-picrylhydrazyl radical scavenging activity, reducing power, and total phenolic content. The acteoside content tended to be higher in the 100% ethanol extract of O. fragrans compared to those with the other extraction conditions tested. Overall, almost all extracts prepared with ethanolic solvents tended to produce better antioxidant activity than those prepared with hot water. These results suggest that the ethanolic extract of O. fragrans could serve as a potential antioxidant and anti-inflammatory pharmaceutical source, and our validated method would be useful for the quality control of O. fragrans extracts.